Greek Elements in the Religious Phenomena of the Eastern Hallstatt Circle - Potrebica, Hrvoje (Array, 2001)
There is a group of general elements that are recognisable in almost all of the Early Iron Age cultures of southeastern Europe and Mediterranean. Although the origin of those elements is a complex question that is discussed also in this paper, we usually call them Greek because their most developed form is manifested within the complex of Greek culture and religion. Similar elements are also visible in certain religious phenomena of the Early Iron Age cultures located north of the area traditionally reached by the Greek influence. This paper deals with presence of such elements within the complex of the Eastern Hallstatt Circle. Based on a case study of several important sites paper discusses the origin of such influences and their meaning within the cultural framework of the Eastern Hallstatt Circle. Perhaps some of the religious elements that we recognise as Greek, in fact came from this area. Some of the similar features can be reflection of the ancient Indo-European common heritage or they are similar products of independent cultural and religious development. In case of those elements that have their source in Greece, paper discusses the manner in which such elements travelled over great distances and how they function within the context of each culture. The most important category for this kind of analysis is burial customs. Beside some material features of burial customs that are common in this area, we can also establish certain conceptual unity. Especially important is the Cult of Heroes (and everything connected to it). The other important religious element is the ceremonial feast (purely sacrificial or more similar to Greek symposium). There is also powerful and omnipotent symbolism of the bull, sometimes connected with the solar cult.